2018
DOI: 10.3389/fonc.2018.00614
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities of EF24, a Novel Curcumin Analog: A Review

Abstract: Curcumin is an attractive agent due to its multiple bioactivities. However, the low oral bioavailability and efficacy profile hinders its clinical application. To improve the bioavailability, many analogs of curcumin have been developed, among which EF24 is an excellent representative. EF24 has enhanced bioavailability over curcumin and shows more potent bioactivity, including anti-cancer, anti-inflammatory, and anti-bacterial. EF24 inhibits tumor growth by inducing cell cycle arrest and apoptosis, mainly thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 101 publications
1
54
0
Order By: Relevance
“…However, few of those clinical trials showed positive outcomes [7], mainly due to its low solubility and poor bioavailability (<1%) [8]. Demethoxycurcumin (DMC) and diphenyl difluoroketone (EF-24) are natural and synthetic CUR analogues, respectively, that display multiple potent bioactivities and increased bioavailability compared to CUR [9,10]. For example, EF-24 was reported to have higher oral bioavailability (60%) and to be much safer than a chemotherapeutic drug in mice [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few of those clinical trials showed positive outcomes [7], mainly due to its low solubility and poor bioavailability (<1%) [8]. Demethoxycurcumin (DMC) and diphenyl difluoroketone (EF-24) are natural and synthetic CUR analogues, respectively, that display multiple potent bioactivities and increased bioavailability compared to CUR [9,10]. For example, EF-24 was reported to have higher oral bioavailability (60%) and to be much safer than a chemotherapeutic drug in mice [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, EF-24 exhibited a 10~20-fold lower 50% growth inhibitory concentration (IC 50 ) than CUR in various solid tumor cells including ovarian, cervical, lung, breast, and prostate cancer cells [13][14][15][16]. Although these two CUR analogues, EF-24 and DMC, were reported to inhibit the proliferation of various solid tumor cells in in vitro and in vivo models [9,10], the precise impacts of these analogues on non-solid tumors, particularly AML, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In endothelial progenitor cells, MHY2233 was shown to decrease acetylated p53 and downstream p21 expression, and to increase expression of FOXO3a, a transcription factor that enhances Sirt1 transcription and leads to decreased p16 expression [197]. The curcumin analogue EF24, that also possesses senolytic activities as described thereafter, has the ability to counteract major inflammatory pathways [219].…”
Section: Msc Rejuvenating Strategiesmentioning
confidence: 97%
“…[16][17][18] Curcumin and its analogs EF24 and EF31 are also toxic, and there are huge defects in drug metabolism. [19][20][21] Therefore, finding a new type of IKKβ/NF-κB inhibitor with high efficiency and low toxicity, and exploring if it can reverse the resistance of gemcitabine has become our main research goal.…”
Section: Introductionmentioning
confidence: 99%